ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN KINERJA DI LAPAS DAN RUTAN - Fikri Firmansyah; Mitro Subroto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Research on leadership has existed since World War II, but there are still differences of opinion. This difference of opinion can be caused by each person having different teachings. The same is true between leadership and management differences. The study of leadership began in the time of Aristotle, while management began in the 20th century with the birth of industrial society. The research method used is descriptive method, namely by describing in general the facts found, then analyzed based on the theories put forward by experts who have an analysis of the problems to be studied. While the data collection techniques carried out by the author in this study can be done by means of library research and field studies. Ideal leadership is a dream or hope for every organization. There are 8 (eight) ideal leadership characters, namely: intelligent, responsible, honest, trustworthy, initiative, consistent, firm and straightforward. Character is a key determinant in the success of an correctional institution. This will bring blessings to all members of the correctional institution in it. The progress and the retreat, the success and failure of the organization are largely determined by the leaders, because the leader is the determinant of the direction and direction that the correctional institution wants to achieve towards the goals to be achieved.